Analysis of the Effect of Intellectual Intelligence and Emotional Intelligence in Improving Msme Business Success in Citraland Bagya City Medan - August Halomoan Siregar; Jenny (Enrichment : Journal of Management, 2022)
The purpose of this research is to find out how the influence given by intellectual intelligence and emotional intelligence in increasing the business success of MSMEs at the Citraland Bagya City Medan Complex. The research method that will be used is descriptive quantitative, while the data collection method used is a questionnaire which will then be measured with a Likert scale. The data analysis technique used is multiple linear regression analysis, partial testing, simultaneous testing and testing the coefficient of determination. The results of this study indicate that partially or simultaneously the variables of intellectual intelligence and emotional intelligence have a significant influence on the success of the UMKM business in the Citraland Bagya City Medan complex.